Impact of Solar Activity on Snow Cover Variation Over the Tibetan Plateau and Linkage to the Summer Precipitation in China - Song, Yan; Li, Zhicai; Gu, Yu; Xiao, Ziniu (Frontiers in Earth Science, 2022)
The snow cover over the Tibetan Plateau is an important physical factor affecting the East Asian climate. However, on interdecadal time scale, its connection to the China summer precipitation may vary and present obvious differences in spatial correlation patterns. It is likely that other external forcing factors may play an important role in regulating the connection. Solar activity is one of the main external forcing factors to drive the Earth's climate system to change. At present, there is little research on the connection between solar activity and snow cover over the Tibetan Plateau. Through correlation analyses, it is found that there are significant synchronous or lag correlations between snow indices and solar parameters on multi-time scales. In particular, the Spring Snow Day Number (SSDN) is of significant synchronous or lag correlation with Solar Radio Flux (SRF), Solar Sunspot Number (SSN) and Total Solar Irradiance (TSI) on multi-time scales. It is further found that SSDN over the Tibetan Plateau has more stable positive correlations with SRF using 21-year running mean and cross spectrum analyses. Therefore, SSDN can be ascertained to be the most sensitive snow index to the solar activity compared with other snow indices. Moreover, its influence on summer precipitation of China is strongly regulated by solar activity. In high solar activity years (HSAY), the significant correlated area of summer precipitation in China to SSDN is located further north than that in low solar activity years (LSAY). Such impact by solar activity is more remarkable after excluding strong ENSO events.